Internet use and breast cancer survivors - Muhamad, Mazanah; Afshari, Mojgan; Mohamed, Nor Aini (The Turkish Online Journal of Educational Technology, 2011)
A survey was administered to 400 breast cancer survivors at hospitals and support group meetings in Peninsular Malaysia to explore their level of Internet use and factors related to the Internet use by breast cancer survivors. Findings of this study indicated that about 22.5% of breast cancer survivors used Internet to get information about breast health issues. They had access to computer in their more personalized spaces such as at their home and in their workplace. Breast cancer survivors tended to use Internet to get information about cancer and treatment options especially on radiotherapy, chemotherapy, health management, treatment side effects and dietary practice. Majority of Internet users believed that information on the Internet were not useful to improve their knowledge about health care issues. Also, significant relationships exist between level of Internet use and five independent variables, including, age, education level, annual income, residence, and race/ethnicity. It is suggested that health care providers should realize how Web-based intervention programs can help breast cancer patients and then encourage patients to use Internet to get highly information to integrate them into their medical and psychological care.